Galician Republicans and their Impression on Montevideo’s Cultural Life - Facal, Silvia (Madrygal. Revista de Estudios Gallegos, 2020)
The Spanish Civil War is the fratricidal conflict that has had the most repercussions in Uruguay because of the strong involvement, in favor of the Republican side, of a large part of the country's population. Although, at the beginning, the government of Gabriel Terra was reluctant to admit the exiled Spanish Republicans, the Uruguayan population offered its help to those who arrived on these coasts of the Río de la Plata and to those who were still fighting in Spain. Most of the Spanish Republican exiles arrived in Uruguay during the conflict and in the following years came from regions such as Catalonia, Euskadi, the two Castiles, Asturias, Andalusia, Madrid and Galicia; and among them stood out the presence of intellectuals, scientists, writers, artists and professionals of all kinds apart from agricultural laborers, merchants, waiters, etc. Throughout this paper we will talk about the migratory experience, in particular, of the Galician republican exiles in Montevideo. The objective of this article is to present the migratory experience, specifically, of the Galician republican exiles in Montevideo. We will make special emphasis on the role that these exiles played in the local cultural scene at the time.
Keywords: Galician People; Republicans; Montevideo; Uruguay; Culture